Indicadores de qualidade do solo de parte dos lotes do assentamento rural companheiro Keno, Jacarezinho/PR: uma sintese inacabada - Barros, Carlos Eduardo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The current model of agricultural production in Brasil, propelled during the 1970's through the Green Revolution, brought and deepened some of the problems in the countryside, be they social and/or environmental. In the context of the contest for land, the countrymen lean towards exclusion in the productive process, in detriment of the agribusiness. As for the environmental matters, we highlight soil and water contamination through agrochemicals, accelerated erosion, exacerbated use of transgenics, among other issues. On this context, life in/of soil might be compromised, as well as agricultural production and the maintenance of the farm laborers. The objective of this research was to analyze the chemical, physical and biological properties as indicators of soil quality in 20 lots on the rural settlement Companheiro Keno in the city of Jacarezinho/PR, with a view to the implementation of agroecological management. It is considered that the adoption of this practice can not only recover and preserve said resource, well as serve as a factor to add value to the products, thus increasing the income, guaranteeing the maintenance of the settled in the field. For chemical analyzes, in each of the lots two simple samples were obtained that generated a compound, being analyzed: pH, Organic Carbon, N, CTC, V%, H + Al. The sampling plot occurred in areas declared by the peasants as being of economic interest. They were held textural analysis and soil density. The macrofauna was obtained according to the methodology proposed by Aquino (2001). The general information about the production, soil management, among others, were obtained from a semi-structured questionnaire. The main results indicate that the quality of the soils of the settlement is compromised: they present low fertility, acidity and compaction. Macrofauna has been shown to be an efficient indicator of soil quality...

O atual modelo de produção agrícola no Brasil, impulsionado durante a década de 1970 pela bandeira da Revolução Verde, trouxe e aprofundou ainda mais alguns problemas socioambientais no campo. No contexto da disputa pela terra, os camponeses tendem a serem excluídos do processo produtivo, em detrimento do agronegócio. Quanto às questões ambientais, elencam-se a contaminação do solo e água por agrotóxicos, erosão acelerada, uso exacerbado de transgênicos, entre outros problemas. Nesse contexto, a vida no/do solo pode ficar comprometida, bem como a produção agrícola e a manutenção do homem no campo. Desta forma, o objetivo geral dessa pesquisa foi analisar algumas propriedades químicas, físicas e biológicas como indicadores de qualidade do solo em 20 lotes do Assentamento Rural Companheiro Keno, município de Jacarezinho/PR, com vistas na implementação do manejo agroecológico. Justifica-se que a adoção dessa prática pode não somente recuperar e conservar o referido recurso, mas também aumentar a renda do assentado e as condição para sua manutenção no campo. Para as análises químicas, em cada um dos lotes foram obtidas duas amostras simples que gerou uma composta, onde foram analisados: pH, Carbono Orgânico, N, CTC, V%, H + Al. A parcela amostral se deu em áreas declaradas pelo camponês como de interesse econômico. Foram realizadas ainda análise textural e densidade do solo. A macrofauna foi obtida de acordo com o metodologia proposta por Aquino (2001). As informações gerais quanto a produção, manejo do solo, entre outros, foram obtidas a partir de um questionário semiestruturado. Os principais resultados apontam que a qualidade dos solos do assentamento está comprometida: apresentam baixa fertilidade, acidez e compactação. A macrofauna demonstrou ser um indicador de qualidade do solo eficiente...
Keywords: Solo rural - Uso; Solos - Fertilidade; Ecologia agrícola